Examining the consulting services delivery at Microsoft Consulting Services (MCS) Singapore and recommendations for improvement - Chee, Wah Keat (2009)
Consulting industry remains as a profession shrouded in great deal of mystery (Flemming & Larry, 2005), hidden behind private partnership, client confidentiality and proprietary methods. While many clients continue to spend millions of dollars a year on consulting services, it is ironic to think that the consulting services has never established a standards approach in profession unlike the accounting, engineering or legal professions. What is interesting is that although consulting is a high stake engagement that influences strategic directions of the client, the approach, methodology, intervention approach and analytical methods used by the consulting firms are often proprietary and rest with the core value of the consulting firms. This also is true for the IT consulting industry. Although traditionally IT consulting industry was originated from specialized domain of technical areas, it has since evolved into strategic IT consulting that prompted a shift in consulting engagement business models that fuses both technical and strategic thinking of the IT firm. Technological solution that has once public domain knowledge to certain extend is now an incomplete solution without strategic thinking. This has prompted IT firms to find ways to differentiate themselves in order to undertake IT strategy consulting engagements.